Overexpression of two CDPKs from wild Chinese grapevine enhances powdery mildew resistance in Vitis vinifera and Arabidopsis. Issue 5 (26th March 2021) - Hu, Yang; Cheng, Yuan; Yu, Xuena; Liu, Jie; Yang, Lushan; Gao, Yurong; Ke, Guihua; Zhou, Min; Mu, Bo; Xiao, Shunyuan; Wang, Yuejin; Wen, Ying‐Qiang
Summary: Calcium‐dependent protein kinases (CDPKs) play vital roles in metabolic regulations and stimuli responses in plants. However, little is known about their function in grapevine. Here, we report that VpCDPK9 and VpCDPK13, two paralogous CDPKs from Vitis pseudoreticulata accession Baihe‐35‐1, appear to positively regulate powdery mildew resistance. The transcription of them in leaves of 'Baihe‐35‐1' were differentially induced upon powdery mildew infection. Overexpression of VpCDPK9‐YFP or VpCDPK13‐YFP in the V. vinifera susceptible cultivar Thompson Seedless resulted in enhanced resistance to powdery mildew (YFP, yellow fluorescent protein). This might be due to elevation of SA and ethylene production, and excess accumulation of H2 O2 and callose in penetrated epidermal cells and/or the mesophyll cells underneath. Ectopic expression of VpCDPK9‐YFP in Arabidopsis resulted in varied degrees of reduced stature, pre‐mature senescence and enhanced powdery mildew resistance. However, these phenotypes were abolished in VpCDPK9‐YFP transgenic lines impaired in SA signaling ( pad4sid2 ) or ethylene signaling ( ein2 ). Moreover, both of VpCDPK9 and VpCDPK13 were found to interact with and potentially phosphorylate VpMAPK3, VpMAPK6, VpACS1 and VpACS2 in vivo (ACS, 1‐aminocyclopropane‐1‐carboxylic acid (ACC) synthase; MAPK, mitogen‐activated protein kinase). These results suggest that VpCDPK9 and VpCDPK13 contribute to powdery mildew resistance via positively regulating SA and ethylene signaling in grapevine.